Well-being, Poverty and Justice from a Child's Perspective : 3rd World Vision Children Study - Andresen, Sabine; Fegter, Susann; Hurrelmann, Klaus; Schneekloth, Ulrich (Children's Well-Being: Indicators and Research, 2017)
This book presents evidence that children are the real experts of their lives. 2600 boys and girls in Germany between the ages of 6 of 11 years, with and without a migration background, were interviewed. Next to established topics of family, friends, leisure time and school, the focus of this study was on the topic of justice. Children were asked what justice in their opinion was and whether they felt treated justly or not. The 3rd World Vision Study puts the subjective well-being of children into the focus and shows that children are able to report competently and authentically about their lives. This volume is of great important to researchers, policy makers and professionals interested in children's well-being from children's own perspectives.